2019
DOI: 10.1097/ccm.0000000000003830
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Patient Outcomes of Pharmacist Participation in Multidisciplinary Critical Care Teams: A Systematic Review and Meta-Analysis*

Abstract: Objectives: The objective of this systematic review and meta-analysis was to assess the effects of including critical care pharmacists in multidisciplinary ICU teams on clinical outcomes including mortality, ICU length of stay, and adverse drug events. Data Sources: PubMed, EMBASE, and references from previous relevant systematic studies. Study Selection: We included randomized controlled trials and nonrando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
145
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(158 citation statements)
references
References 45 publications
2
145
0
11
Order By: Relevance
“…Patients admitted to the intensive care unit (ICU) are at higher risk for developing DRPs, from 2.1/1,000 to 804.5/1,000 patients days (Garrouste-Orgeas et al, 2010;Garrouste-Orgeas et al, 2015;Garrouste-Orgeas et al, 2016), primarily cause by their critical diseases status or complications, the use of various high alert medications, and the rapid changing pharmacotherapies (Kari et al, 2018). Previous studies have shown that critical care pharmacists can play an essential role in promoting the delivery of pharmaceutical care (PC) and improve the overall quality of health care by offering individualized recommendations in complicated drug regimens, reducing the incidence rate of DRPs, and decreasing preventable ADEs (Tasaka et al, 2018;Lee et al, 2019;Reinau et al, 2019). However, the development of PC in the ICU is currently facing three major challenges worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Patients admitted to the intensive care unit (ICU) are at higher risk for developing DRPs, from 2.1/1,000 to 804.5/1,000 patients days (Garrouste-Orgeas et al, 2010;Garrouste-Orgeas et al, 2015;Garrouste-Orgeas et al, 2016), primarily cause by their critical diseases status or complications, the use of various high alert medications, and the rapid changing pharmacotherapies (Kari et al, 2018). Previous studies have shown that critical care pharmacists can play an essential role in promoting the delivery of pharmaceutical care (PC) and improve the overall quality of health care by offering individualized recommendations in complicated drug regimens, reducing the incidence rate of DRPs, and decreasing preventable ADEs (Tasaka et al, 2018;Lee et al, 2019;Reinau et al, 2019). However, the development of PC in the ICU is currently facing three major challenges worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The positive impact of clinical pharmacists, specifically in critical care and in medical and emergency services has been clearly documented; their impact is reflected in reducing drug costs, provides vital educational function and provides continuous and individualized pharmacotherapeutic care. 32,33 The majority of the participants agreed that the services of clinical pharmacy influence the safety and effectiveness of patient care alongside decreasing morbidity and mortality. 33,34 The clinical pharmacy services should be extended to cover all various specialties and medical departments in the KSA.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 The majority of the participants agreed that the services of clinical pharmacy influence the safety and effectiveness of patient care alongside decreasing morbidity and mortality. 33,34 The clinical pharmacy services should be extended to cover all various specialties and medical departments in the KSA. Unfortunately, most of Alomi YA, et al: Clinical Pharmacy Practice Administration and Management in Saudi Arabia the hospitals had no assistant at their satellite services in clinical pharmacy services.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of the pharmacists on patient care had been proved by many studies [10,[18][19][20][21]. Lee et al reported that including critical care pharmacists in the multidisciplinary ICU team improved patient outcomes including mortality, ICU length of stay in mixed ICUs, and preventable/non-preventable adverse drug events [22]. In our study, after pharmacist attendance, the rate of antimicrobial agent utilizations in the discharged patients decreased and patient antibiotic charges including the total drug costs were saving per stay.…”
Section: Discussionmentioning
confidence: 99%